Nothing to lose - Child, Lee (Jack Reacher novel., 2014)
When he arrives in the small town of Despair, Colorado, Jack Reacher finds himself taking on an entire town as he searches for the truths behind its sinister connection to a brutal war that is killing Americans many miles away.